Phenology of the Valência and Virgínia peanut botanic genotypes - Cavalcanti dos Santos, Roseane; de Albuquerque Melo Filho, Péricles; Marsicano de Brito, Socorro de Fátima; de Sousa Moraes, Joselito (Pesquisa Agropecuaria Brasileira, 1997)
Development stage descriptions were studied in peanuts (Arachis hypogaea, L.) of the Valência and Virgínia botanic types based on phenological events. The stages proposed were germination (G), appearing of the first tetrafoliates leaves (AF), appearing of the first branches (AR), beginning bloom (IF), beginning peg (AG), lenghthening peg (ALG), beginning pod (IFV), final flowering (FF) and full pod maturity (MCV). The G, AF and AR stages showed short differences among both Valência and Virgínia group cultivars. AP and ALP took place seven and ten days after IF in both types studied. Beginning bloom took place 29 days after sowing (das) in Valência versus 33 in Virgínia genotypes. IFV and FF occurred 47 and 74 days in Valência, respectively. In Virgínia, IFV and FF occurred 52 and 95 days, after sowing. MCV differed among types within 24 days. The greatest differences among botanical types studied, as to phenological stages, occurred at the reproductive phase.